2008
DOI: 10.1002/ibd.20376
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin is useful in predicting disease relapse in pediatric inflammatory bowel disease

Abstract: FC levels differentiate active IBD from controls. Among children with CD and in remission, FC levels may be useful in predicting impending clinical relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 38 publications
2
61
0
8
Order By: Relevance
“…Others have obtained similar fecal calprotectin concentration in both diseases [12,15,26,28] or directed attention to the strong correlation between the activity disease in patients with CD [13,29]. Kosiara and Komraus [14,27] have observed lower average concentration of fecal calprotectin in patients with CD; however, other authors have noted in patients in remission higher content of fecal calprotectin in patients with CD [12,20,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have obtained similar fecal calprotectin concentration in both diseases [12,15,26,28] or directed attention to the strong correlation between the activity disease in patients with CD [13,29]. Kosiara and Komraus [14,27] have observed lower average concentration of fecal calprotectin in patients with CD; however, other authors have noted in patients in remission higher content of fecal calprotectin in patients with CD [12,20,26].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the authors postulate that the correlation between fecal calprotectin concentration and the activity of the disease is stronger in the case of UC than in CD, which is linked with a rare involvement of the large intestine and with a lack of a complete mucosal healing even in remission phase [7,23,25]. Others have obtained similar fecal calprotectin concentration in both diseases [12,15,26,28] or directed attention to the strong correlation between the activity disease in patients with CD [13,29]. Kosiara and Komraus [14,27] have observed lower average concentration of fecal calprotectin in patients with CD; however, other authors have noted in patients in remission higher content of fecal calprotectin in patients with CD [12,20,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A FC value above 400 µg/g in asymptomatic CD patients, predicted relapse within 9 months of collection in 89% of patients (95% confidence interval [CI] 51.8-99.7, p = 0.03) compared to no clinical relapse within 9 months when FC values were below 400 µg/g. 47 Similarly, van Rheenen 48 reported that teenagers with a FC above 500 µg/g had a 53% (10/19) risk of progressing to symptomatic relapse within 3 months, whereas a value below 500 µg/g only had a 12% (5/43) risk of symptomatic relapse. A retrospective analysis of 73 children with IBD found that a FC concentration of 275 µg/g had sensitivity and negative predictive value (NPV) of 97% and specificity and a positive predictive value (PPV) of 97%, with a likelihood ratio of 6.4 for predicting IBD relapse.…”
Section: A Marker Of Inflammatory Bowel Diseasementioning
confidence: 98%
“…A few investigators took a step forward to evaluate FC as a predictive marker of IBD relapse in children. Walkiewicz et al 47 examined 32 children with IBD, 11 of those with CD. A FC value above 400 µg/g in asymptomatic CD patients, predicted relapse within 9 months of collection in 89% of patients (95% confidence interval [CI] 51.8-99.7, p = 0.03) compared to no clinical relapse within 9 months when FC values were below 400 µg/g.…”
Section: A Marker Of Inflammatory Bowel Diseasementioning
confidence: 99%